Selection of the complex of enzyme preparation for the hydrolysis of the constituents of grain at the fermentation of the wort of high - Mudrak, Tatiana; Kuts, Anatoly; Kovalchuk, Svitlana; Kyrylenko, Roman; Bondar, Nikolai (My University, 2018)
In this work we have selected the optimal complex of enzyme preparations for hydrolysis of constituents of grain raw materials at fermentation of wort of high concentrations. In the selection of enzyme systems, their effect on the technical and chemical parameters of mature broods during fermentation of wort is investigated. For research, corn starch of 69.0% was used. Based on experimental studies, it was found that the use of a complex of enzyme preparations - amylolytic Amylex 4T, saccharifying - Diazim TGA, proteolytic (Alfalase AFP), cytolytic (Laminex 750) and complex complex AF β-glucanase and xylanase XL combinations of their concentrations contributed to the intensification of the fermentation process of the wort and increase the accumulation of the target product - ethanol by 0.8-1.4%, depending on the concentration of the wort. The highest amount of ethanol was accumulated at the maximum dosage of additional enzyme preparations.
Keywords: enzyme preparation; highly concentrated wort; starch; dry matter; fermentation; кафедра біотехнології продуктів бродіння і виноробства; кафедра готельно-ресторанної справи